Legal Consequences of Sale and Purchase Using Guardianship Declaration Made by Not an Authorized Official - Firdaus, Mohamad Bayu; Riyanto, Taufan Fajar (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Abstract. Land sale and purchase transactions involving minors must meet certain legal requirements, including the use of a valid guardianship letter. However, in practice, it is still found that the use of a Guardianship Certificate made by someone other than an authorized official does not meet the provisions of the law, thus causing legal consequences for the validity of the deed of sale and purchase. The purpose of this study is to analyze the considerations of the panel of judges in Decision Number 100/Pdt.G/2021/PN.Skt which cancels the sale and purchase of land rights using a guardianship certificate made not by an authorized official, and to analyze the legal consequences of the sale and purchase deed using a guardianship certificate made not by an authorized official. This study uses a normative legal research type which is carried out by examining library materials or secondary data. The data analysis method used in this study is qualitative with the Statute Approach method and the Case Approach. The results of this study are that the Sale and Purchase Deed Number is considered legally invalid because at that time one of the selling parties had not reached the age recognized by law to enter into an agreement. The Panel of Judges canceled the sale and purchase transaction using a guardianship certificate made not by an authorized official which was considered legally invalid because it did not fulfill the correct legal procedures related to the guardianship of minors, resulting in the sale and purchase deed and land ownership certificate products being legally invalid.Keywords: Certificate of guardianship; Deed of sale and purchase; Legal consequences.